Analisis Peran Ekonomi Kreatif: Subsektor Kriya, Kuliner, Fesyen, Penerbitan, dan Seni Rupa Terhadap Ekspor di Indonesia Tahun 2011-2021 - Johan, Benedict (PARAHYANGAN ECONOMIC DEVELOPMENT REVIEW, 2023)
The creative economy has been recognized as a sector with great potential as it has contributed 7.8% for economic growth. In this study, the role of creative economy development on exports in Indonesia is identified through the Gross Domestic Product variable and the average wage per creative economy subsector. The data for this study were obtained from the Ministry of Tourism and Creative Economy and the Central Bureau of Statistics for the period 2011-2021. This study uses panel data and the GLS (Generalized Least Square) method. The results show that in this study wages significantly negatively affect exports, but GDP does not significantly affect exports.